Pengaruh Financial Literacy, Locus of Control, Income, dan Hedonism Lifestyle terhadap Financial Management Behavior Generasi Z - Novia Regita Cahyani (Jurnal Ilmu Manajemen, 2022)
Population growth is a factor that can affect economic growth, where increasing people's purchasing power results in consumptive behaviour because the development of the times and technology in the current era of globalization brings changes and progress in all things. This study aims to analyze the influence of financial literacy, locus of control, income, and hedonism lifestyle on the financial management behaviour of the Z generation in East Java. This quantitative conclusive causality research and data analysis technique use multiple linear regression. The sample number was 422 respondents using quota sampling, data obtained by distributing an online questionnaire. The findings show that there is an influence of financial literacy, locus of control, and hedonism lifestyle on financial management behaviour. Still, there is no influence of income on financial management behaviour. This study implies that by understanding the factors that influence financial management, the community, especially the Z generation, is expected to improve their financial management behaviour to achieve financial welfare.